REKOMENDASI LOKASI SHELTER KARANTINA MANDIRI SEBAGAI UPAYA MITIGASI PENYEBARAN COVID19 PADA PERMUKIMAN PADAT DI PESISIR UTARA KOTA SEMARANG - Surya Tri Esthi Hutama; Muhammad Indra Hadi; Angrenggani Pramitasari; Arif Ganda Purnama (Jurnal Riptek, 2020)
COVID 19 pandemics has huge implications on population all over the world, not to mention in a densely populated area like North Semarang. Living in overcrowded housing as a consequence of the rapid urban population growth has put people at higher risk of COVID19 outbreak. In other side the community with daily earning still have to work for meets family needs. Other factors which worsen is occurrence of rob flood regularly. Monitored from the recent situation of COVID-19 pandemic, daily-normal social activities have increased the numbers of COVID 19 infection in certain areas, will get worse in overcrowded areas with limited space and amenities. The Health protocol for infected people requiring them to do self-quarantine, thus they need separate space and facilities (shelter). The limited condition of dense residential areas, so that community do not allow self quarantine independently. The aim of this paper is to find alternatives shelter location using spatial method analysis, which considers health protocol and community characteristics. The results show there are four recommendations of shelter locations that suitable for the community to do self-quarantine.